Correlation of histopathological findings in azoospermic males undergoing microsurgical testicular sperm extraction and sperm retrieval rate: a retrospective study - Mishra, Devanshi; Vyas, Sameer; Keshri, Rajshree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Male factor is the sole cause of infertility in 20% cases, and a contributory cause in 30-40% cases of infertility. Azoospermia is the absence of sperms in semen and it affects around 1% males. With the advent of procedures like testicular sperm aspiration (TESA) and microsurgical testicular sperm extraction (M-TESE), surgical sperm retrieval (SSR) has been made possible and such men can father their own genetic offspring with the help ofiIn vitro-fertilization-intra-cytoplasmic sperm injection (IVF-ICSI). Tissue can also be cryopreserved for use in future. Histopathological evaluation of testicular tissue obtained on diagnostic testicular biopsy/ M-TESE can help to predict the probability of finding sperms, the underlying etiology of azoospermia and also to establish obstructive (OA) cause when in doubt. Methods: This is a retrospective analysis of database of 34 azoospermic males who underwent MTESE between year 2015- 2023 and for whom histopathology was done. Results: In this study, SSR rate was 41.17%. The most common histopathological finding was Sertoli cell only syndrome in 41.1% cases (sperm retrieval rate 14.2%) followed by normal spermatogenesis in 17% cases (sperms found in 100% cases). Maturation arrest was found in 11.7% cases with sperms found in 25% cases. The study is limited by small sample size. Conclusions: The histopathology of testicular tissue can provide valuable insights into predicting SSR rate and establishing diagnosis of OA etiology in azoospermia.